2012
DOI: 10.1515/jpm-2012-0247
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of rupture of fetal membranes (ROM): a meta-analysis

Abstract: Aim: The aim of this study was to compare the performance of tests based on the detection of insulin-like growth factor binding protein 1 (IGFBP-1) and placental α -microglobulin-1 (PAMG-1) in diagnosing rupture of fetal membranes (ROM) across different patient populations. Methods: A meta-analysis was conducted on prospective observational or cohort studies investigating ROM tests based on the detection of IGFBP-1 and PAMG-1 meeting the following criteria: (1) performance metrics calculated by comparing resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…Direct visualization of liquor passage through the external cervical os during speculum examination is definitive, but this is not possible in every case. Thus, many tests has been advised for diagnosis of PROM, however, each one has its own limitations, making the diagnosis of PROM difficult (Ramsauer et al, 2013).…”
Section: Results:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct visualization of liquor passage through the external cervical os during speculum examination is definitive, but this is not possible in every case. Thus, many tests has been advised for diagnosis of PROM, however, each one has its own limitations, making the diagnosis of PROM difficult (Ramsauer et al, 2013).…”
Section: Results:-mentioning
confidence: 99%
“…PROM has a considerable incidence rate, and is responsible for serious morbidities and mortalities to both the mother and her fetus. Based on these findings, premature rupture of membranes has been the scope of many studies, but its diagnosis remains a dilemma (Ramsauer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are clinically relevant to practice because the greatest economic value of PAMG-1 will be derived from nonobvious or inconclusive cases. 10,12,18 We acknowledge that there are several limitations of our study. Instead of determining cost-effectiveness with cost and clinical outcomes or cost and quality-adjusted life years, we purely focused on cost and cost comparison.…”
Section: Obstetrics Researchmentioning
confidence: 96%
“…21 Literature has shown that PAMG-1 is highly accurate in diagnosing ROM with superior test characteristics. 7,8,[15][16][17][18][19] It is imperative to note that in most publications evaluating CTDT, the abovereported sensitivity was calculated using specimens from laboring subjects in which there was certainty about the diagnosis of ROM. 36 For example, the sensitivity for the fern test was 51% and 98% in nonlaboring and laboring patients, respectively.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation